CRISPR/Cas9 systems: Delivery technologies and biomedical applications - Yimin Du; Yanfei Liu; Jiaxin Hu; Xingxing Peng; Zhenbao Liu (Elsevier, 2023)
The emergence of the clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein 9 (Cas9) genome-editing system has brought about a significant revolution in the realm of managing human diseases, establishing animal models, and so on. To fully harness the potential of this potent gene-editing tool, ensuring efficient and secure delivery to the target site is paramount. Consequently, developing effective delivery methods for the CRISPR/Cas9 system has become a critical area of research. In this review, we present a comprehensive outline of delivery strategies and discuss their biomedical applications in the CRISPR/Cas9 system. We also provide an in-depth analysis of physical, viral vector, and non-viral vector delivery strategies, including plasmid-, mRNA- and protein-based approach. In addition, we illustrate the biomedical applications of the CRISPR/Cas9 system. This review highlights the key factors affecting the delivery process and the current challenges facing the CRISPR/Cas9 system, while also delineating future directions and prospects that could inspire innovative delivery strategies. This review aims to provide new insights and ideas for advancing CRISPR/Cas9-based delivery strategies and to facilitate breakthroughs in biomedical research and therapeutic applications.